Ambisense gene expression from recombinant rabies virus: random packaging of positive- and negative-strand ribonucleoprotein complexes into rabies virions. - Finke, S (1997)
We have recovered from cDNA a rabies virus (RV) containing identical, transcriptionally active promoters at its genome (negative-strand) and antigenome RNA and directing efficient expression of a chloramphenicol acetyltransferase (CAT) reporter gene from the antigenome. Transcription of the antigenome CAT gene was terminated by a modified RV gene junction able to mediate transcription stop and polyadenylation but not reinitiation of downstream transcripts. While in standard RV-infected cells genome and antigenome RNAs were present in a 49:1 ratio, the ambisense virus directed synthesis of equal amounts of genome and antigenome RNA (1:1). Total replicative synthesis was reduced by a factor of less than 2, revealing an unexpectedly high level of replication activity of the transcriptionally active promoter in the absence of the parental antigenome promoter. Successful packaging of ambisense ribonucleoprotein complexes (RNPs) into virions demonstrated that the parental 5' end of the RV genome RNA does not contain putative signals required for incorporation into virions. As determined both for standard RV and ambisense RV, virus particles contained genome and antigenome RNPs in the same ratios as those present in infected cells (49:1 and 1:1, respectively), indicating indiscriminate incorporation of RNPs independent of signals in the RNA. Ambisense expression of multiple foreign genes from RV vectors may circumvent problems with transcriptional attenuation of rhabdovirus housekeeping genes.